Symbolic Violation in the poetry of Majed Al-Hassan - Naill Abdulhussein Abdulsayed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Violation represents one of the main properties of poetics. The concept of poetics is multi-dimensional due to different linguistic usage in the text. The structural violation is dominant in the poetic text. What we realize in Majid Al-Hassan’s poetry is the use of the lexical item that is transferred to a symbol making use of linguistic violation to convey vast spaces of meaning by changing it to a textual symbol full of discourse and expressive charge that takes them to far horizons away from their independent existence in the text.